The bear that wouldn't growl - Rayner, Shoo (Heinemann Oxford, 1997)
A pack of four stories in a series which provides a reading programme for Key Stages 1 and 2, aiming to combine enjoyable, motivating stories with a carefully developed and consistent progression.